2005
DOI: 10.1152/japplphysiol.00539.2004
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of hydroxyl radical and cyclooxygenase metabolites in the activation of lung vagal sensory receptors by circulatory endotoxin in rats

Abstract: The involvement of hydroxyl radical and cyclooxygenase metabolites in the activation of lung vagal sensory receptors by circulatory endotoxin in rats. J Appl Physiol 98: 620 -628, 2005. First published October 1, 2004; doi:10.1152/japplphysiol.00539.2004.-Circulatory endotoxin can stimulate vagal pulmonary C fibers and rapidly adapting receptors (RARs) in rats, but the underlying mechanisms are not clear. We investigated the involvement of hydroxyl radicals and cyclooxygenase metabolites in the stimulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…Only afferent fibers that showed stimulation within 2 s after the injection were studied. The conduction velocities of the VLCFs identified by this method have been shown to be within the range of C fibers [33], [34]. The general locations of all fibers were identified by their responses to the gentle pressing of the lungs with a saline-wetted cotton Q-tip.…”
Section: Methodsmentioning
confidence: 96%
“…Only afferent fibers that showed stimulation within 2 s after the injection were studied. The conduction velocities of the VLCFs identified by this method have been shown to be within the range of C fibers [33], [34]. The general locations of all fibers were identified by their responses to the gentle pressing of the lungs with a saline-wetted cotton Q-tip.…”
Section: Methodsmentioning
confidence: 96%
“…C-nerve fiber activation often coincides with RAR activation [46], as the two sensory receptors have been shown to respond to similar irritants. RARs are myelinated fibers located in the larynx, trachea, and bronchi [47].…”
Section: Airway Receptorsmentioning
confidence: 99%
“…Endotoxin (Lai et al 2005) and reactive oxygen species (Ruan et al 2005) activate lung C fibers, which alter breathing frequency. Further, studies in humans identified a decrease in variability of respiratory timing with endotoxemia supporting an impact of systemic inflammation on breath-to-breath dynamics (Preas et al 2001).…”
Section: Introductionmentioning
confidence: 99%